Views from Vienna. (2021) - Johnson, Peri Lynne
Abstract : This presentation gives a brief overview of how the International Atomic Energy Agency (IAEA, or Agency) has fulfilled its mandated activities during the pandemic, considering: (1) host country relations; (2) meetings of IAEA policy making organs; (3) other meetings under the auspices of the Agency; and (4) IAEA nuclear verification work, for which the Agency is most well-known.